Religion and media: A critical review of recent developments - Morgan, David (Critical research on religion, 2013)
This article considers recent changes in the definition of religion and of media as the basis for framing the study of their relation to one another and recent research in the intersection they have come to form over the last two decades or so. The history, materiality, and reception of each have colored scholarly work, and made ethnography, practice, material culture, and embodiment key aspects of scholarship. A new paradigm for some scholars for studying mediation is aesthetics—no longer understood as the “philosophy of the beautiful,” but as the study of perception in the mediated practices that make up lived religion.